A Vaccinomics Approach for the Identification of Tick Protective Antigens for the Control of Ixodes ricinus and Dermacentor reticulatus Infestations in Companion Animals - Contreras, Marinela; Villar, Margarita; de la Fuente, José (Frontiers in Physiology, 2019)
Ticks and tick-borne pathogens affect health and welfare of companion animals worldwide, and some human tick-borne diseases are associated with exposure to domestic animals. Vaccines are the most environmentally friendly alternative to acaracides for the control of tick infestations, and to reduce the risk for tick-borne diseases affecting human and animal health. However, vaccines have not been developed or successfully implemented for most vector-borne diseases. The main limitation for the development of effective vaccines is the identification of protective antigens. To address this limitation, in this study we used an experimental approach combining vaccinomics based on transcriptomics and proteomics data with vaccination trials for the identification of tick protective antigens. The study was focused on Ixodes ricinus and Dermacentor reticulatus that infest humans, companion animals and other domestic and wild animals, and transmit disease-causing pathogens. Tick larvae and adult salivary glands were selected for analysis to target tick organs and developmental stages playing a key role during tick life cycle and pathogen infection and transmission. Two I. ricinus (heme lipoprotein and uncharacterized secreted protein) and five D. reticulatus (glypican-like protein, secreted protein involved in homophilic cell adhesion, sulfate/anion exchanger, signal peptidase complex subunit 3, and uncharacterized secreted protein) proteins were identified as the most effective protective antigens based on the criteria of vaccine E > 80%. The putative function of selected protective antigens, which are involved in different biological processes, resulted in vaccines affecting multiple tick developmental stages. These results suggested that the combination of some of these antigens might be considered to increase vaccine efficacy through antigen synergy for the control of tick infestations and potentially affecting pathogen infection and transmission. These antigens were proposed for commercial vaccine development for the control of tick infestations in companion animals, and potentially in other hosts for these tick species.